A bibliometric analysis on the research trends of global climate change and future directions - A. S. L. Lindawati; Meiryani (Cogent Business & Management, 2024)
This paper uses bibliometric methods to quantitatively analyze global scientific performance and current research fields in the field of global climate change. The intention was to enhance knowledge of the scientific understanding of climate change. The data used in this analysis is based on 259 papers by scholars worldwide that were published in 498 academic journals in the Scopus database between 2006 and 2022 to investigate the methods used in scientific research to study climate change. The scientific knowledge, changes in research hotspots, worldwide geographic distribution of research, and country-specific focus are all summarized in our analysis. The findings indicate that (1) Throughout the era under investigation, the goal of research on climate change has evolved from comprehending the climate system to developing climate technology and regulations, like laws and efficient energy use; (2) The idea of climate change is reflected in modern models of energy efficiency, renewable energy transition, carbon pricing, and circular economy. The idea of climate change, seen from an overall viewpoint, affects carbon footprint, social and economic impact, rising carbon dioxide levels, and carbon sequestration; (3) since 2006, research on climate change vulnerability has grown rapidly, and its publications are widely disseminated in numerous source journals; in terms of global climate research change, the Chinese Academy of Sciences and the University of Chinese Academy of Sciences are the two most productive institutions and Water resource-related disputes and collaboration. Our research can be used by scholars and policymakers to investigate future research goals and to consider the current directions of climate change studies. Future studies can address issues related to human health risks, inequality in society and the economy, policy and regulation in the context of global climate change, and the rate at which emissions will zero out. This study's primary goal is to close this gap and improve our comprehension of the body of current literature.
Keywords: 650; Global; climate change; research; scientometric; environmental